Analysis of A Structure Considering Horizontal Setbacks Under Lateral Loading Using Etabs - Prince Kumar Suryavanshi; Rahul Satbhaiya (International Journal of Scientific Research in Civil Engineering, 2021)
The behavior of a multi-storey framed building during strong earthquake motions depends on the distribution of mass, stiffness, and strength in both the horizontal and vertical planes of the building. In multi-storeyed framed buildings, damage from earthquake ground motion generally initiates at locations of structural weaknesses present in the lateral load resisting frames. Further, these weaknesses tend to accentuate and concentrate the structural damage through plasticization that eventually leads to complete collapse. In some cases, these weaknesses may be created by discontinuities in stiffness, strength or mass between adjacent storeys. Such discontinuities between storeys are often associated with sudden variations in the frame geometry along the height. There are many examples of failure of buildings in past earthquakes due to such vertical discontinuities. Irregular configurations either in plan or elevation were often recognized as one of the main causes of failure during past earthquakes. In the present study we are comparing structures with their adjoining conditions known as setback structures. In this study we are considering three different conditions where distance between structures is taken as 0m, 5m and 10m and dynamic analysis is performed using analysis tool ETABS.